1957
DOI: 10.1346/ccmn.1957.0060119
|View full text |Cite
|
Sign up to set email alerts
|

Water-Vapor Adsorption on Clays

Abstract: The distinctive response of clay minerals to water indicated that it should be possible to determine the water sensitivities of sedimentary rock samples directly by watervapor adsorption measm~ments. Therefore, the adsorption of water-vapor by standard clay samples and by core samples fl'om oil-producing formations has been investigated.Water-vapor adsorption isotherms of the montmorillonite and kaolinite samples are characteristic of the clay type and serve as an aid in their identification. The illite isothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1963
1963
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…They were considered to be more representative of the areas in an aqueous medium than BrunauerEmmett-Teller (B.E.T.) values from nitrogen adsorption, which are about 30 per cent higher and show little variation with ionic type (Johansen and Dunning, 1959;Keenan, Mooney, and Wood, 1951). …”
Section: Surface Areasmentioning
confidence: 99%
“…They were considered to be more representative of the areas in an aqueous medium than BrunauerEmmett-Teller (B.E.T.) values from nitrogen adsorption, which are about 30 per cent higher and show little variation with ionic type (Johansen and Dunning, 1959;Keenan, Mooney, and Wood, 1951). …”
Section: Surface Areasmentioning
confidence: 99%
“…For example, Rose (1971) noted that although hysteresis in dry soils may be real and complicated, its effect will be masked by environmental factors such as temperature and can, therefore, be ignored. However, several studies have clearly shown that even under very dry conditions hysteresis occurs in both source clays and soil samples (Arthur et al, 2013;Johansen & Dunning, 1957;Lu & Khorshidi, 2015;Prunty & Bell, 2007;Shvarov & Koreneva, 2008). Consideration of hysteresis under such dry conditions is crucial for accurate modelling of water vapour flow in arid regions (Bittelli et al, 2008), for quantification of soil evaporation (Or, Lehmann, Shahraeeni, & Shokri, 2013) and for ensuring correct estimation of soil properties from hygroscopic water content measurements (Wuddivira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Next, the samples, including the controls, were washed intensively with 0.1 mol dm ±3 NaCl solution and adjusted to pH around 7. Because water vapor adsorption processes strongly depend on kind of exchange ions (Johansen and Dunning, 1959), the samples were finally transferred into homoionic calcium forms. Some properties of calcium form of the soils are presented in Table 2.…”
Section: Methodsmentioning
confidence: 99%